Number and Impact of Published Scholarly Works by Pharmacy Practice Faculty Members at Accredited US Colleges and Schools of Pharmacy (2001-2003) - Coleman, Craig I. (American Journal of Pharmaceutical Education, 2007)
OBJECTIVE: To evaluate the quantity and quality of published literature conducted by pharmacy practice faculty members in US colleges and schools of pharmacy for the years 2001-2003. METHODS: The Web of Science bibliographic database was used to identify publication citations for the years 2001-2003, which were then evaluated in a number of different ways. Faculty members were identified using American Association of Colleges of Pharmacy rosters for the 2000-2001, 2001-2002, and 2002-2003 academic years. RESULTS: Two thousand three hundred seventy-four pharmacy practice faculty members generated 1,896 publications in Web of Science searchable journals. A small number of faculty members (2.1%) were responsible for a large proportion of publications (30.6%), and only 4.9% of faculty members published 2 or more publications in these journals per year. The average impact factor for the top 200 publications was 7.6. CONCLUSION: Pharmacy practice faculty members contributed substantially to the biomedical literature and their work has had an important impact. A substantial portion of this work has come from a small subset of faculty members.